Tanggung Jawab Penginjilan Bagi orang Percaya: Sebuah Refleksi Teologis 1 Korintus 9: 16-17 - Ita Lintarwati; Carolina Etnasari Anjaya; Yonatan Alex Arifianto (KHARISMATA: Jurnal Teologi Pantekosta, 2022)
Evangelism is the duty of every human being because, according to God's plan, all human beings need to be returned to their original design, namely to eternity. However, at present, the meaning of evangelism is experiencing bias and decline in its actualization because the mission of evangelism is used to boast. This study aims to describe and analyze the theological study of evangelism according to the narrative text of 1 Corinthians 9:16-17, and from this study, it is found that in carrying out evangelism, the most important needs are self-denial and a willing heart. Because without self-denial, the mission of evangelism will lead to self-aggrandizement and fulfillment of self-interest. AbstrakPenginjilan merupakan tugas setiap umat manusia karena sesuai rencana Allah, semua manusia perlu dikembalikan kepada rancangan semula yaitu kepada kekekalan. Namun saat ini, makna penginjilan mengalami bias dan kemerosotan dalam aktualisasinya sebab tugas penginjilan justru dijadikan sarana untuk memegahkan diri. Penelitian ini bertujuan mendeskripsikan dan menganalisa kajian teologis penginjilan sesuai narasi teks 1 Korintus 9:16-17 dan dari kajian tersebut ditemukan bahwa dalam menunaikan penginjilan, kebutuhan paling utama adalah penyangkalan diri dan kerelaan hati. Sebab tanpa penyangkalan diri tugas penginjilan akan mengarahkan pada kemegahan diri dan pemenuhan kepentingan diri sendiri.